Implications of Epithelial–Mesenchymal Plasticity for Heterogeneity in Colorectal Cancer - Pereira, Lloyd; Mariadason, John M.; Hannan, Ross D.; Dhillon, Amardeep S. (Frontiers in Oncology, 2015)
Colorectal cancer (CRC) is a genetically heterogeneous disease that develops and progresses through several distinct pathways characterized by genomic instability. In recent years, it has emerged that inherent phenotypic plasticity in some populations of CRC cells can contribute to heterogeneity in differentiation state, metastatic potential, therapeutic response and disease relapse. Such plasticity is thought to arise through interactions between aberrant signaling events, including persistent activation of the APC/β-catenin and KRAS/BRAF/ERK pathways, and the tumour microenvironment. Here, we highlight key concepts and evidence relating to the role of epithelial-mesenchymal plasticity as a driver of CRC progression and stratification of the disease into distinct molecular and clinicopathological subsets.